Distribution of dense bone island in the jaw through panoramic radiography based on gender and age - Otty Ratna Wahyuni; Yunita Savitri; Sri Wigati Mardi Mulyani; Deny Saputra; Ramadhan Hardani Putra; Rasendriya Chandramurti; Alquira Emalda Hardiva (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2022)
Objectives: Panoramic radiographs are used as a diagnostic tool adjunctive to oral examinations, treatment plans, and evaluation of treatment outcomes. This study was aimed to determine the distribution of Dense Bone Island (DBI) in the jaws through panoramic radiography based on gender and age. Materials and Methods: The method used for this research is descriptive-observational. The research data used is secondary data with a total of 422 panoramic radiographic data of RSKGMP Airlangga University patients. Results: From a study of 422 secondary data found 253 (60%) patients with Dense Bone Island in the jaw, more commonly found in female, which is 162 (38.4%) in female patients and 91 (21.5%) in male patients. It was also found mostly in the age range of 17–25 years. Conclusion: Dense Bone Island was found more in female than in male. It was also found to be more common in patients aged 17–25 years.